PENGARUH INOVASI PRODUK, STORE ATMOSPHERE DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN PADA WARUNK UPNORMAL PEKANBARU - M, Aidil Rizki; Alvi, Alwie Furwanti; Henni, Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The rapid development of the culinary business in Indonesia has resulted in increased and tighter competition in the culinary business. It requires culinary businesses to develop and innovate the products offered according to the need and desires of consumers. One of the café that has innovated their product is Warunk Upnormal Pekanbaru. The purpose of this research is to examine the influence of Product Innovation, Store Atmosphere and Word Of Mouth on Purchasing Decisions and Customer Satisfaction at Warunk Upnormal Pekanbaru. The analysis technique used is path analysis and supported by sobel test. The number of samples taken is 100 respondents using purposive sampling method. Data was collected by distributing questionnaires. Based on the result of the research found that Product Innovation Variables, Store Atmosphere and Word Of Mouth has a significant effect on Purchasing Decisions, Purchasing Decision has a significant effect on Customer Satisfaction, and Product Innovation Variables, Store Atmosphere and Word Of Mouth has a significant effect on Customer Satisfaction through Purchasing Decision.Keywords : Product Innovation, Store Atmosphere, Word Of Mouth, Purchasing Decision, Customer Satisfaction.